2010
DOI: 10.1371/journal.pone.0014014
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Costs and Cost-Effectiveness of Tuberculosis Treatment in DOTS and Non-DOTS Facilities in Rio de Janeiro, Brazil

Abstract: BackgroundCosts of tuberculosis diagnosis and treatment may represent a significant burden for the poor and for the health system in resource-poor countries.ObjectivesThe aim of this study was to analyze patients' costs of tuberculosis care and to estimate the incremental cost-effectiveness ratio (ICER) of the directly observed treatment (DOT) strategy per completed treatment in Rio de Janeiro, Brazil.MethodsWe interviewed 218 adult patients with bacteriologically confirmed pulmonary tuberculosis. Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 7 publications
6
75
0
7
Order By: Relevance
“…This review showed that treatment completion rates were most likely to exceed 90% when treatment was based on a patient-centred approach using DOT. Similar benefits of DOT were also reported by Steffen and colleagues who compared treatment completion rates of persons using self-administered treatment (SAT) facilities in Rio de Janeiro, Brazil [14] . Treatment completion rates were 71% in SAT facilities and 79% in DOT facilities.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This review showed that treatment completion rates were most likely to exceed 90% when treatment was based on a patient-centred approach using DOT. Similar benefits of DOT were also reported by Steffen and colleagues who compared treatment completion rates of persons using self-administered treatment (SAT) facilities in Rio de Janeiro, Brazil [14] . Treatment completion rates were 71% in SAT facilities and 79% in DOT facilities.…”
Section: Discussionsupporting
confidence: 74%
“…In SAT facilities, the costs per completed treatment were US$ 194 for patients and US$ 189 for the health system, compared to US$ 336 and US$ 726 in DOT facilities. The ICER was US$ 6 616 per completed DOT treatment compared to SAT [14] .…”
Section: Discussionmentioning
confidence: 99%
“…These factors might be related to knowledge or understanding of the disease, its treatment, and the importance of treatment adherence, as well as to the costs of treatment for patients and their families. (21) The present study has some limitations. The reduced number of some exposures and some outcomes did not allow the evaluation of factors independently predictive of outcomes.…”
mentioning
confidence: 81%
“…Diabetes mellitus, in addition to increasing mortality, has been described as being related to delayed sputum conversion, increased chances of recurrence, and increased chances of developing multidrug-resistant tuberculosis. (21) Socioeconomic factors also increased the probability of unfavorable outcomes. Among the patients with a lower income and a lower level of education, the rate of treatment abandonment was higher, as was the rate of treatment failure, which might be associated with poor treatment adherence even without abandonment.…”
mentioning
confidence: 99%
“…El gasto de bolsillo más elevado para los pacientes que reciben tratamiento bajo la terapia DOTS en la investigación realizada por Ukwaja y col. (11) en una población nigeriana, fue el correspondiente al transporte, por un valor de 83 200 COP, similar a lo observado en el presente estudio en las ciudades de Medellín y Quibdó. Algo parecido se pudo observar en el estudio realizado por Steffen y col. (12) , en Brasil, donde los costos directos más altos fueron el trasporte y la medicación no TB, con 33 054 COP y 32 153 COP, respectivamente.…”
Section: Discussionunclassified